HAK ULAYAT LAUT: FENOMENA YANG PERLU DICERMATI DALAM MENYUSUN KADASTER KELAUTAN - Tanjung Nugroho; Eko Budi Wahyono; Ign. Indradi (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
The phenomena on sea tenure by the traditional society in Nusantara maritime are spread from the western part upto the eastern area. The common property rights on maritime resources have not been explicitly admitted by the state, however,they are only considered as the state property. According to maritime anthropologists, the practice of sea tenure constitutesstrategies of resources management. This is intended to preserve the fishermen’s living conditions and marine resources. To acertain extent, the fish resources are said to belong to all people and openly accessed. This has led to a great crisis on fisheriesand if this is not well controlled there will be human disasters.Keywords: sea tenure, marine cadastre.